Inhibitory effects of Homalomena occulta essential oil against Streptococcus pyogenes, Streptococcus pneumoniae, and Candida albicans and formulation of health care products - Nguyễn, Thị Ái Nhung; Nguyễn, Trần Thiên Phú; Nguyễn, Vũ Bảo Ngọc; Trần, Quang Huy; Nguyễn, Đại Châu; Nguyễn, Công Kính; Tôn, Thất Hữu Đạt; Nguyễn, Thanh Hải (Hue University Journal of Science: Natural Science, 2026)
In this study, essential oil was extracted from Homalomena occulta and evaluated for its antimicrobial potential. The essential oil was obtained by means of steam distillation, and its chemical constituents were analysed by using GC–MS. Forty compounds were identified, with linalool, terpinen-4-ol, 3-carene, and α-terpineol being the predominant components, accounting for 25.15, 6.68, 3.60, and 3.55%, respectively. In vitro assays demonstrated that H. occulta essential oil exhibited significant inhibitory activity against the throat pathogen Streptococcus pyogenes and the respiratory pathogen Streptococcus pneumoniae, with MIC values of 400 µg.mL⁻¹ and corresponding MBC values of 400 µg.mL⁻¹ and 800 µg.mL⁻¹, respectively. Additionally, the oil showed strong antifungal activity against Candida albicans, a yeast responsible for mucocutaneous infections, with MIC being 200 µg.mL⁻¹ and MFC being 400 µg.mL⁻¹. Furthermore, preliminary formulation trials were conducted to develop value-added products incorporating H. occulta essential oil, including a medicated balm for alleviating dermatitis, itching, muscle pain, and body warming, as well as aromatic candles with deodorising and relaxation effects. These findings highlight the promising potential of H. occulta essential oil for application in natural health-care product development, ensuring safety and aligning with sustainable development goals.